Short-term Reduction of Adult Zebra Mussels, Dreissena polymorpha, in the Hudson River Near Catskill, New York: An Effect of Juvenile Blue Crab (Callinectes Sapidus) Predation? - D. P. Molloy; Powell, J.; Ambrose, P. (Journal of Shellfish Research, 1994)
During the summer of 1992, a loss of 2- to 3-cm zebra mussels, Dreissena polymorpha, was recorded in the Hudson River near Catskill, NY. We document this adult population crash and present field and laboratory data suggesting that predation by blue crabs, Callinectes sapidus, was responsible. Dredge samples on July 8th indicated that the mean density of the largest zebra mussel size class (length = 2 to 3 cm) in the Hamburg-Catskill-Germantownregion was 664 m-2 (range of 59 to 2,222 m-2, 14rucks examined). In sharp contrast, extensive dredging on August II th did not recover a single mussel of that size class in that area. The largest mussel collected on August 11th was only 0.7 em long, with over 100 rocks examined. An abundance of shell fragments and detached, live mussels were considered evidence of predation, possibly by a large immigrant blue crab population present in the area. Laboratory trials confirmed that these crabs can aggressively consume zebra mussels, particularly the size class that was virtually eliminated in the Catskill area, and that their feeding does result in piles of shell fragments and removed, yet unconsumed mussels. Further supportive evidence of the blue crab predation hypothesis was gained in the summers of 1993 and 1994, when blue crabs did not migrate into the Catskill area and a massive decline in 2 to 3 cm mussels did not occur.
Keywords: Biological control; blue crabs; predation; Zebra mussels